Advanced speaking (Thành phố Hồ Chí Minh, 2013)
This course provides advanced-level students with language and practice activities which will lead to higher band scores in the IELTS Speaking test. The course also contains tips and advice for engaging in a conversation-style test, where the skills of listening to the questions and responding appropriately are very important.
Keywords: Tiếng Anh,English language,English language,Tiếng Anh; Kỳ thi,Hưỡng dẫn học tập,Examinations,Study guides,Spoken English,Nói tiếng Anh